CO2 storage in carbonates: Wettability of calcite. (July 2017) - Arif, Muhammad; Lebedev, Maxim; Barifcani, Ahmed; Iglauer, Stefan
Graphical abstract: Highlights: Effect of pressure on CO2 -wettbailtiy of calcite was investigated. Effect of temperature on CO2 -wettbailtiy of calcite was investigated. Effect of salinity and surface roughness on CO2 -wettbailtiy of calcite was investigated. Abstract: Limestone reservoirs are considered as potential candidates for CO2 geo-sequestration. In order to predict structural and residual trapping capacities of CO2 and containment security in carbonates, the wettability of the CO2 /brine/rock systems plays a vital role. Calcite is the main component in limestone and thus commonly used to characterize carbonate wettability using direct contact angle measurements. Previously, several studies determined wettability of calcite/CO2 /brine systems, but the data clearly lacks in terms of (a) wettability characterization for a wide range of operating conditions, and (b) published data reports contradicting results with measured wettability ranging from strongly water-wet to weakly CO2 -wet. Thus, to reduce the uncertainty in the reported measurements, we conducted an experimental study to measure advancing and receding water contact angles for calcite/CO2 /brine systems as a function of pressure (0.1–20 MPa), temperature (308–343 K) and salinity (0 wt% NaCl – 20 wt% NaCl). The results indicate that calcite is strongly water-wet at ambient conditions and with the increase in pressure the surface gradually loses its water-wetness. At high pressure storage conditions (20 MPa and 308 K), calcite surface turned weakly CO2 -wet implying that an upwards directed suction force will be created and consequently leakage may occur. Moreover, with the increase in temperature contact angle decreased implying that carbonates turn more water-wet at higher temperatures. Furthermore, contact angle increased with salinity. By comparing our results with published data, we point out that apart from pressure, temperature and salinity, the surface cleaning methods and surface roughness and nature of the sample itself can be possible sources of ambiguity in literature data. We conclude that high temperature and low salinity carbonate formations with lower injection pressures are more suitable for safe CO2 storage.